2018
DOI: 10.1124/mol.118.112953
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Is a Potent Activator of KCNQ3 and KCNQ5 Potassium Channels

Abstract: IntroductionGabapentin (Neurontin) and pregabalin (Lyrica) are synthetic antiepileptic and antinociceptive gabapentinoid compounds originally designed as analogues of the neurotransmitter γ-aminobutyric acid (GABA), and both are in widespread clinical use (Calandre et al., 2016). However, the mechanisms of action of gabapentinoids, exemplified by gabapentin and pregabalin, are incompletely understood. [ 3 H]-gabapentin binding was first described in membrane fractions from rat brain homogenates, and the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 50 publications
1
39
0
2
Order By: Relevance
“…If these findings are also observed in humans, the M-channel would be a rational therapeutic target for inflammatory airway diseases. In support of this idea, a recent study has shown that gabapentin, a neuromodulator previously found to be effective for treatment of refractory chronic cough in patients (61), potently activates M-channels composed of KCNQ3, KCNQ5 homomers, or KCNQ2/3 heteromers (62). Moreover, airway smooth muscle cells also express functional KCNQ/K v 7 channels, and activating these channels by flupirtine or retigabine has been shown to attenuate the histamine-induced constriction of human airways (63) and relax muscarinic-evoked airway contraction in rodents (64,65).…”
Section: Discussionmentioning
confidence: 86%
“…If these findings are also observed in humans, the M-channel would be a rational therapeutic target for inflammatory airway diseases. In support of this idea, a recent study has shown that gabapentin, a neuromodulator previously found to be effective for treatment of refractory chronic cough in patients (61), potently activates M-channels composed of KCNQ3, KCNQ5 homomers, or KCNQ2/3 heteromers (62). Moreover, airway smooth muscle cells also express functional KCNQ/K v 7 channels, and activating these channels by flupirtine or retigabine has been shown to attenuate the histamine-induced constriction of human airways (63) and relax muscarinic-evoked airway contraction in rodents (64,65).…”
Section: Discussionmentioning
confidence: 86%
“…The results obtained revealed that injection of either Lv-shGAS5 or Lv-miR-135a-5p significantly prolonged the epileptic latency and reduced the frequency of seizures. Although the implications of KCNQ3 and potassium channels in the pathogenesis of epilepsy have been illustrated in many studies, [35][36][37] the antiepileptic drugs dealing with potassium channels are still under investigated. This study highlighted a novel molecule mechanism that Lv-miR-135a-5p and Lv-shGAS5 are able to inhibit KCNQ3 expression in the rat models of epileptic seizure (Figure 4), indicating that downregulation of lncRNA GAS5 can decrease KCNQ3 through sponging miR-135a-5p to prolong latent period and to reduce seizure frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Voltage-gated potassium (Kv) channels within the Kv channel subfamily Q (KCNQ), also termed the Kv7 subfamily, are sensitive to activation by a range of small molecules, including synthetic drugs, neurotransmitters, and metabolites (9)(10)(11)(12)(13). Kv channels, including the 5 isoforms within the KCNQ (Kv7) subfamily, are composed of tetramers of pore-forming (a) subunits, each consisting of 6 transmembrane segments (S): S1-4 comprise the voltage-sensing domain (VSD), and S5-6 comprise the pore module ( Fig.…”
mentioning
confidence: 99%